Projecting impacts of two-wheelers on urban air quality of Douala, Cameroon. (May 2017) - Adiang, Cyrille Mezoue; Monkam, David; Njeugna, Ebenezer; Gokhale, Sharad
Graphical abstract: Highlights: Gompertz traffic, semi-empirical emission and CALINE4 air quality models are applied. The World Bank CO levels of 2002 are validated by back projecting 2008 traffic flow. Two-wheelers significantly impacting urban air quality are investigated for Douala city. Emission reduction scenario with Euro-III due to two-wheelers is modelled. Abstract: Douala, one of the fastest developing cities of Cameroon, has been experiencing unprecedented growth of two-wheelers (motorbikes) and poor perceived air quality. The city has no air quality monitoring system and no air quality data. The only survey that reported the carbon monoxide (CO) levels was carried out by the World Bank under the Clean Air Initiative in 2002 and another study of traffic counts in 2008. In this study, the World Bank CO concentration levels of 2002 have been validated by back projecting the 2008 traffic scenario using vehicular emission and line source dispersion models and future scenarios up to 2015 have been projected at one of the busiest traffic intersections. The potential impacts of Euro emissions standards to improve the roadside air quality in Douala were studied. The results showed that the CO levels increased by a factor of 18 for a period from 2002 to 2015 with an annual increase of 65% in two-wheelers and 31% in cars. The estimated population of two-wheelers in 2015 was found to be 23 times higher than in 2002, which, by 2035, is expected to grow by 533% and the car ownership by 146%. If Euro II and III emissions standards are gradually implemented on two-wheelers in Cameroon, CO levels along roadways are expected to be reduced by about 70%. These results may be helpful to policy makers to prepare an air quality management plan for the city.